About Modeling the Excitation Conditions of Cherenkov and Diffraction Radiations in Periodic Metal-dielectric Structures - G.S. Vorobjov; M.V. Petrovskyi; A.I. Ruban; D.Y. Doroshenko (Журнал нано- та електронної фізики)
General procedure for modeling the excitation conditions of Cherenkov and diffraction radiations in periodic metal-dielectric structures is described. It is based on the representation of the electron beam space-charge wave in the form of a dielectric waveguide surface-wave. On the experimental facility of millimeter-wave the basic modes of excitation conditions of spatial harmonics of the Cherenkov and diffraction radiations are simulated. The method is tested by comparing the numerical analysis and experimental results on the layout of the device of the orotron type - generator of diffraction radiation.